Pure small cell carcinoma of the prostate: A rare tumor - Simone Albisinni (Indian Journal of Urology, 2012)
Pure small cell carcinoma of the prostate is a rare and aggressive neoplasm, with only few cases described in literature and poor prognosis: mean survival is 5 months. We report the case of a patient with this disease, with special attention to the evolution of neuroendocrine markers as Chromogranine A and neuron-specific enolase during the progression of the tumor, evaluating their possible role in staging and follow up.